A study on droplet deposition of nano DAP using unmanned aerial hybrid sprayer on peanut (Arachis hypogaea) crop - P, RAJESH; MOHANKUMAR, A P; KAVITHA, R; SUTHAKAR, B; SURRENDRAKUMAR, A; GANESAN, K (The Indian Journal of Agricultural Sciences, 2025)
The experiment was conducted during rainy (kharif) seasons of 2023 and 2024 at Tamil Nadu Agricultural University, Coimbatore, Tamil Nadu to study the application of nano DAP using a hybrid drone in groundnut (Arachis hypogaea L.) crops. The UAV, model DH-AG-H1, equipped with a 12 L sprayer tank and a 16,000 mAh battery. The UAV’s performance was assessed across multiple parameters, including spray droplet deposition rate, droplet size distribution, density, area coverage, uniformity and drift characteristics. The UAV operated at a spray height of 1 m and a forward speed of 3 m/s, achieved an operational efficiency of 4.11 ha/h. Results showed that in kharif 2023 season, droplet densities ranging from 35–76 drops/cm² in the target zone, with minimal horizontal drift (0–22 drops/cm²) and very low vertical drift (0–6 drops/cm²). The kharif 2024 season data indicated droplet densities from 31–70 drops/cm² in the target zone, with horizontal drift ranging from 0–20 drops/cm² and vertical drift from 0–14 drops/cm². The hybrid drone demonstrated VMD/NMD ratios from 1.02–1.66 and droplet densities between 31 and 76 drops/cm², indicating effective coverage with a diverse range of droplet sizes, from very fine to ultra-coarse. These results confirmed the UAV’s precision in reducing fertilizer use, soil compaction and chemical drift, highlighting its efficiency in promoting sustainable agriculture.